Implementation of a Machine Learning with a Python Programming Approach to Predict the Level of Disease Cases - Ridwan; Prio Kustanto (Green Publisher, 2024)
Digital transformation invariably results in the development of data-driven insights. To counteract digital transformation in the health domain, tools that can perform predictive analysis are needed. The use of machine learning to predict the severity of a disease can aid in the prompt formulation of health care policies. Machine learning models employ several techniques in classification algorithms with a framework provided by the Python programming language. In this case, the used data include a dataset that was collected from the Indonesian Health Profile, which includes information on health-related behaviors, health-related laws, and sociodemographic trends. Decision tree modeling has very good accuracy when classifying the severity of illness.